Oscillatory mechanics in very preterm infants on continuous positive airway pressure support: Reference values. Issue 3 (1st December 2022) - Zannin, Emanuela; Rigotti, Camilla; Neumann, Roland P.; Dellacà, Raffaele L.; Schulzke, Sven; Ventura, Maria L.
Abstract: Objective: To create reference values for respiratory system resistance (Rrs) and reactance (Xrs) measured by the forced oscillation technique (FOT) in nonintubated very preterm infants. Design: Retrospective analysis of data collected as part of prospective observational studies in two centers. Setting: Tertiary neonatal intensive care units. Patients: Non‐intubated infants below 32 weeks' gestation age who did not develop bronchopulmonary dysplasia. Interventions: We applied FOT using a mechanical ventilator (Fabian HFOi; Vyaire) that superimposed small‐amplitude oscillations (10 Hz) on a continuous positive airway pressure of 3 and 5 cmH2 O. Measurements were performed during regular tidal breathing using a face mask. Main outcome measures: We analyzed 198 measurements performed between 7 postnatal days and 40 weeks postmenstrual age (PMA) in 85 infants, with a median (Q1, Q3) gestational age of 30.43 (29.14, 31.18) weeks. Logarithmic transformations were applied to Rrs and Xrs, and the relationship between transformed impedance values and demographic factors was examined by backwards stepwise linear regression. Results: In univariable analysis, transformed Xrs was significantly associated with PMA, postnatal age, weight, and length, while Rrs was not. The best multivariable regression model estimating transformed Xrs (cmH2 O*s/L) at continuous positive airway pressure (CPAP) = 5 cmH2 O was: Ln(50 − Xrs) = 4.536 − 0.009 x PMA − 0.014 x weight z ‐score. SEE = 0.053, R 2  = 0.36. The mean (SD) Rrs at CPAP = 5 cmH2 O was 33.63 (5.28) cmH2 O*s/L. Conclusion: We have established reference values for Rrs and Xrs at 10 Hz in nonintubated preterm neonates on continuous positive airway pressure support.